Development Model of Competence Test Expertise for Light Vehicle Techniques for Vocational Teachers - Asyari, Chasan; Made Sudana, I; Syamwil, Rodia (Universitas Negeri Semarang, 2018)
_______________________________________________________________The growth of the automotive industry is growing, so the demands for the availability of skilled vocational graduates are increasing, so that teachers who are competent and productive are needed. The problems that occur are the limited number of productive teachers, so that the competency test development model is needed. The purpose of this study: (1). Knowing the competency profile of TKR teachers, (2). Knowing the results of developing competency test models for vocational school teachers in the TKR field, (3). Conduct the effectiveness test of the development model of the TKR Vocational School teacher competency test.The method used is R & D with desaign post test-only technique. Tests carried out are tests of validity, normality, and effectiveness.Conclusion: (1). The professional competence profile of TKR teachers in the electricity sector at a fairly good level, (2). Model development is declared valid, so that the competency test model in the form of TKR modules is obtained, especially electricity, (3). The development model is effective in implementing TKR teacher competency tests